Sosialisasi Penggunaan ATM Beras Untuk Membantu Penyaluran Zakat - Azran Budi Arief; Andani Achmad; Zaenab Muslimin; Merna Baharuddin; Ejah Umraeni Salam; Ansar Suyuti; Ida Rachmaniar S; Elyas Palantei; Syafruddin Syarif; Dewiani Dewiani; Ardiaty Arief; Ikhlas Kitta; Faizal A. Samman; Salama Manjang; Muh. Bachtiar Nappu; Gassing Gassing; Yusran Yusran; Rhiza S. Sadjad; Irwan Setiawan; Fighi S. Permadi; Muh Anshar (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2022)
Zakat distribution is an activity that is often carried out around the community. At the time of distribution, of course, it takes a long time and can cause queues to be less efficient. To overcome all of that, an ID card-based Rice ATM was created to facilitate the distribution of zakat in the form of rice. By using microcontrollers, ultrasonic sensors, DC motors and web applications. This web application aims to record the identity of the community and also regulate the ration of rice distribution for each citizen. This service was carried out in Parang Bugisi Village, Tinggi Muzzle District, Gowa Regency, South Sulawesi Province. The method begins with conducting socialization activities and giving questionnaires. There were 4 questions used in the questionnaire to determine the level of knowledge of participants. Furthermore, the socialization participants can practice directly the use of Rice ATMs. From the results of the questionnaire before the socialization activity, the majority of participants did not know about the Rice ATM and after participating in the socialization activity, the majority of participants began to understand, it was seen that in the results of the questionnaire there was an increase in understanding of the way it works, benefits and users of the Rice ATM by 86%, 76%, 81% and 52%, respectively.